2013
DOI: 10.1109/tim.2013.2248289
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Calibration of Undersampled Pipelined ADCs by Frequency Domain Filtering

Abstract: Integral nonlinearity (INL) is used for the post-correction of pipeline analog-digital converters (ADC)s. An input-frequencydependent INL model is developed for the compensation. The model consists of a static term that is dependent on the ADC output code and a dynamic term that has an additional dependence on the input signal frequency. The INL model is subtracted from the digital output for post-correction. The static compensation is implemented with a look-up-table (LUT). The dynamic calibration is performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It was found that superior static compensation results can be obtained for one of the investigated ADCs if a more representative static model (i.e., HCF modeling) was developed. This observation was subsequently confirmed in [10], where tangible improvements (over [2]) were obtained with a static correction when the actual HCF data were used instead of the HCF model in [9].…”
Section: A State-of-the-art Inl Modelingmentioning
confidence: 63%
See 2 more Smart Citations
“…It was found that superior static compensation results can be obtained for one of the investigated ADCs if a more representative static model (i.e., HCF modeling) was developed. This observation was subsequently confirmed in [10], where tangible improvements (over [2]) were obtained with a static correction when the actual HCF data were used instead of the HCF model in [9].…”
Section: A State-of-the-art Inl Modelingmentioning
confidence: 63%
“…These actions are not performed in the straight-forward methods developed here, particularly the minimization process. However, the HCF data of ADC1 is very small in magnitude and it was shown that the ADC1 HCF has no perceivable effect on the (static) calibration in [10]. In general, the Gaussian function-based model yielded better modeling results than the sinc approach because it has …”
Section: Model Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In [4], a simplified Volterra model was obtained by forcing hi1,i2,,ioo=0 for i 2 , i 3 , …, i o ≠ 0 in (1). This model is also used in [9], though in the frequency domain, as described in Subsection III.A in that paper.…”
Section: Reduced‐complexity Volterra Kernelsmentioning
confidence: 99%